Desain Geometrik Jalan Pada Jalan Kebun Kopi – Toboli Sulawesi Tengah - Hikmansyah, Syahrun; Mallawangeng, Tamrin; Yunianti, Nurhadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The Kebun Kopi - Toboli road section is a crucial route connecting several districts in Central Sulawesi. This section consists of straight roads interspersed with several sharp curves, causing inconvenience to road users. Therefore, redesigning the geometrics is essential. The objective of this research is to redesign the geometric configuration of the existing Kebun Kopi - Toboli section, from STA 10+965 to STA 11+150. This research employs a literature review method to examine applicable standards, a field survey method to obtain geometric data, and a computational model simulation using Autodesk Civil 3D software to calculate various geometric variables. The results of the horizontal alignment calculations on the existing road section, particularly on the curves, show a total length of 300 meters. The terrain classification for the proposed road is flat, with a design speed of 60 km/h and an existing road width of 2x2.5 meters. The section includes 5 Spiral-Spiral curves. For vertical alignment, there are 5 concave vertical alignments and 4 convex vertical alignments.